2012
DOI: 10.1016/j.compositesb.2011.11.057
|View full text |Cite
|
Sign up to set email alerts
|

Gradient design of metal hollow sphere (MHS) foams with density gradients

Abstract: SMetal hollow sphere (MHS) structures with a density gradient have attracted increasing attention in the effort to pursue improved energy absorption properties. In this paper, dynamic crushing of MHS structures are discussed. MHS of different gradients are modelled by stacks of hollow spheres of the same external diameter but different wall thicknesses in the crushing direction. Then based on the dynamic performance of MHS structures with uniform density, a crude semi-empirical model is developed, showing the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 63 publications
(21 citation statements)
references
References 26 publications
0
20
0
1
Order By: Relevance
“…The full densification can be determined by the last main local maxima point, with the corresponding strain as the densification strain [34].…”
Section: Finite Element Methods Simulationmentioning
confidence: 99%
“…The full densification can be determined by the last main local maxima point, with the corresponding strain as the densification strain [34].…”
Section: Finite Element Methods Simulationmentioning
confidence: 99%
“…Thus, the layers of the structure are crushed progressively (layer by layer) [7,27]. On the other hand, it has to be mentioned that the distribution of the cells (horizontal and vertical distance of the cells) has a great impact on the mechanical properties of TMFs [17].…”
Section: Parametric Studymentioning
confidence: 99%
“…Many researchers have focused on the different combinations of reinforcement and matrix while some others are dealing with the effects of hollow sphere size and distribution on the mechanical properties and energy absorption capability [3,6]. It has been reported that energy absorbing properties of MMSFs can be customized by the appropriate selection of matrix and heat treatment procedure as well as the reinforcement composition, wall thickness, diameter and volume fraction [7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…The foam core provides not only the transverse pressure, but also the bending/shear strength during the coupled deformation between the core compression and the beam bending/stretching phases. Moreover, researches show that the responses of the foam at the impact or distal ends are different for different impacting conditions (Liu and Zhang, 2009;Liu, et al, 2012), which indicates that the pressures loads on the back and front faces due to the transverse compression of the core may be different, and asynchronous. As a result, how to consider the bending/shear effect of the foam core during the deformation, and describe the transverse pressures on the face sheets caused by the core compression, are the key points in the analytical modeling of sandwich beams, and have not been absolutely solved to per author's knowledge.…”
Section: Introductionmentioning
confidence: 99%